Comparative analysis of the fit quality of monolithic zirconia veneers produced through traditional and digital workflows using silicone replica technique: an in vitro study - Tri Minh Doan; Tan Ngoc Nguyen; Van-Khoa Pham; Natdhanai Chotprasert; Chau Tran Bao Vu (BMC Oral Health, 2024)
Abstract Background The success of a restoration largely depends on the quality of its fit. This study aimed to investigate the fit quality of monolithic zirconia veneers (MZVs) produced through traditional and digital workflows. Methods A typodont maxillary right central incisor was prepared. The maxillary arch with the prepared tooth was scanned with Trios 3 Pod intra-oral scanner (IOS), which served as a pattern to create thirty 3D resin models through printing. Additionally, thirty conventional impressions of the maxillary with the prepared tooth were taken using polyvinyl siloxane (PVS) impression material. These impressions were cast using dental gypsum products to create thirty stone dies, which were then scanned externally. Sixty MZVs were milled from multi-layered zirconia disks. The marginal and internal gaps of restorations were assessed using the silicone replica technique. Results The highest marginal accuracy for both the conventional and digital impression groups was observed in the cervical area, with values of 74.6 μm and 61.9 μm, respectively. The smallest internal gaps for both groups were also recorded in the cervical area, at 109.9 μm for the conventional group and 109.7 μm for the digital group. The digital group exhibited better marginal fit, particularly in the incisal and mesial areas (79.3 μm and 75.7 μm, respectively), compared to the conventional group (88.1 μm and 90.8 μm). No statistically significant differences in internal fit were observed. Conclusion MZVs fabricated using the digital workflow exhibited superior marginal fit compared to those fabricated using the conventional workflow, though both techniques yielded clinically acceptable results.